2010
DOI: 10.1007/s12040-010-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dissolved carbohydrates and uronic acids in a tropical estuary, India

Abstract: Carbohydrates including uronic acids are among the active components of dissolved organic carbon, and play an important role in biogeochemical cycling of organic carbon in marine environments. In order to understand their distribution, concentrations of total dissolved carbohydrate (TCHO), dissolved polysaccharide (PCHO), dissolved monosaccharide (MCHO), and dissolved uronic acid (URA) were measured in the Mandovi estuary, west coast of India during the monsoon and premonsoon seasons. The estuary experienced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
(103 reference statements)
1
8
1
5
Order By: Relevance
“…The high proportion of PCHO to TCHO (92%À96%) in the tributaries was in contrast to that found in riverine environments (Hung et al 2005;Gu eguen et al 2006), suggesting that not all carbohydrates originate from the decomposition products of soil litter (Hedges et al 1994). The contribution of TCHO to DOC is defined as the carbohydrate yield (Khodse et al 2010;Wu & Yang 2013) and varied from 6% to 34% in the present study, close to the range (15%À30%) recorded for freshly derived organic matter from phytoplankton (Pakulski & Benner 1994). Thus, the high proportion of PCHO to TCHO may be due to the in situ production of high-molecular-weight PCHO compounds by phytoplankton or bacteria (Hung et al 2003;Guimarães et al 2013).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The high proportion of PCHO to TCHO (92%À96%) in the tributaries was in contrast to that found in riverine environments (Hung et al 2005;Gu eguen et al 2006), suggesting that not all carbohydrates originate from the decomposition products of soil litter (Hedges et al 1994). The contribution of TCHO to DOC is defined as the carbohydrate yield (Khodse et al 2010;Wu & Yang 2013) and varied from 6% to 34% in the present study, close to the range (15%À30%) recorded for freshly derived organic matter from phytoplankton (Pakulski & Benner 1994). Thus, the high proportion of PCHO to TCHO may be due to the in situ production of high-molecular-weight PCHO compounds by phytoplankton or bacteria (Hung et al 2003;Guimarães et al 2013).…”
supporting
confidence: 85%
“…Chrost et al (1989) observed that the highest concentration of total dissolved carbohydrates (TCHO) occurred shortly after the peak of phytoplankton biomass. Furthermore, a significant negative correlation between bacterial abundance (BA) and the ratio of total dissolved carbohydrates to dissolved organic carbon (TCHO/DOC) was observed in the Mandovi estuary (Khodse et al 2010). Allochthonous DOC is composed extensively of humic substances, which can be measured by specific ultraviolet absorbance (SUVA 254 ); therefore, it has been considered recalcitrant (Moran & Hodson 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D-amino acids are derived from bacterial cell wall, and bacterial macromolecules but are absent in phytoplankton or vascular plants (Kaiser and Benner, 2008). In the Mandovi estuary, a shift in the ecosystem production from net heterotrophy to net autotrophy occurs during the pre-moonsoon season (Khodse et al, 2010). The higher D-amino acid concentration observed during the pre-monsoon season (Table 2) indicate that accumulation of bacterial remnants due to diagenetic processes was not the reason for the observed higher D-amino acids concentrations in the Mandovi estuary.…”
Section: D-amino Acid Concentration and Compositionmentioning
confidence: 99%
“…TDCHO accounts for a significant fraction of the DOC pool in both oceanic waters (20 to 30%) (Pakulski & Benner 1992) and estuarine waters (9 to 60%) , Khodse et al 2010. Heterotrophic bacteria use TDCHO as a source of carbon and energy (Hanisch et al 1996, Amon et al 2001).…”
Section: Introductionmentioning
confidence: 99%